Male Partners’ Involvement Towards Prenatal Screening And Diagnostic Testing For Down Syndrome - Kusumaningrum, Niken; Choi, Christina; Yeo, George S.H. (Department of Nursing, Faculty of Medicine, Diponegoro University, 2014)
Introduction: Now, male partners’ involvement in prenatal screening and diagnostic testing for Down syndrome is becoming increasingly recognized as well to ensure that parents are well informed of the risks and benefits of screening. The aim of study was to understand the degree of male partners’ involvement during pregnancy in Singapore population. Methods: A cross-sectional survey of male partners’ attending prenatal counseling was performed. The instrument used to measure the level of involvement is a self-assessment questionnaire that identifies the role of male partners with a Likert scale. Descriptive statistics was used to analyze data gained. Result: A total of 107 participants completed the questionnaire. Sixty-seven percent of male partners were found to have a highlevel of involvement while 32.7% was found to have a medium level of involvement. Most of them stated that women can pursue prenatal testing without their permission. Male partners found it more important for them to accompany their spouse to amniocentesis or CVS than to the Down syndrome screening test. When participants were asked about how much information about Down syndrome they sought prior to the appointment, how much discussion they had with their spouse about Down syndrome testing, and about whether they or their spouse should be the first person to receive test results, most stated that they were undecided. Conclusion: These results revealed that male partners were very well involved in the Down syndrome testing during pregnancy and future studies should assess possible underlying factors that influence male partners’ involvement.